Evaluation on the cost-effective threshold of osteoporosis treatment on elderly women in China using discrete event simulation model. Issue 2 (February 2017) - Ni, W.; Jiang, Y.
Abstract Summary This study used a simulation model to determine the cost-effective threshold of fracture risk to treat osteoporosis among elderly Chinese women. Osteoporosis treatment is cost-effective among average-risk women who are at least 75 years old and above-average-risk women who are younger than 75 years old. Introduction Aging of the Chinese population is imposing increasing economic burden of osteoporosis. This study evaluated the cost-effectiveness of osteoporosis treatment among the senior Chinese women population. Methods A discrete event simulation model using age-specific probabilities of hip fracture, clinical vertebral fracture, wrist fracture, humerus fracture, and other fracture; costs (2015 US dollars); and quality-adjusted life years (QALYs) was used to assess the cost-effectiveness of osteoporosis treatment. Incremental cost-effectiveness ratio (ICER) was calculated. The willingness to pay (WTP) for a QALY in China was compared with the calculated ICER to decide the cost-effectiveness. To determine the absolute 10-year hip fracture probability at which the osteoporosis treatment became cost-effective, average age-specific probabilities for all fractures were multiplied by a relative risk (RR) that was systematically varied from 0 to 10 until the WTP threshold was observed for treatment relative to no intervention. Sensitivity analyses were also performed to evaluate the impacts from WTP and annual treatment costs. Results In baseline analysis, simulated ICERs were higher than the WTP threshold among Chinese women younger than 75, but much lower than the WTP among the older population. Sensitivity analyses indicated that cost-effectiveness could vary due to a higher WTP threshold or a lower annual treatment cost. A 30 % increase in WTP or a 30 % reduction in annual treatment costs will make osteoporosis treatment cost-effective for Chinese women population from 55 to 85. Conclusions The current study provides evidence that osteoporosis treatment is cost-effective among a subpopulation of Chinese senior women. The results also indicate that the cost-effectiveness of using osteoporosis treatment is sensitive to the WTP threshold and annual treatment costs.